Safety improvement through root cause analysis and hazard control in lift installation - Gurning, Valentino Bernardus; Safitri, Dian Mardi (Universitas Sultan Ageng Tirtayasa, 2025)
The performance of construction projects is evaluated based on the effectiveness and efficiency of project completion, considering cost, schedule, quality, and safety. Elevator installation work is classified as high-risk and poses a potential for fatalities if safety protocols are not followed. To address these critical safety challenges, this research aims to control hazards and propose solutions using the Root Cause Analysis and Hazard Control approach. This approach involves identifying the hazard, assessing its source, and implementing interventions and controls to enhance work safety. Based on the analysis of alternative solutions, administrative controls and personal protective equipment (PPE) are prioritized, accounting for 31.8% of the measures to improve work safety. However, elimination and substitution measures, at 18.2%, are also critical to achieving higher safety standards. This research has limitations, including project delays during the research process, which necessitate further development to identify unaddressed risks.